Enmattered Virtues. (21st May 2018) - Fiecconi, Elena Cagnoli
I argue that, for Aristotle, virtues of character like bravery and generosity are, like the emotions, properties that require a hylomorphic analysis. In order to understand what the virtues are and how they come about, one needs to take into account their formal components and their material components. The formal component of a virtue of character is a psychic disposition, its material component is the appropriate state and composition of the blood. I defend this thesis against two potential objections and I show that it is relevant for a study of Aristotle's ethics.